PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL INTERAKTIF BERORIENTASI KEARIFAN LOKAL PADA MATERI BUMI KITA TERANCAM BAHAYA MATA PELAJARAN IPAS KELAS VI - Ni Ketut Sudewi Apriliantari; Komang Trisna Mahartini; Putu Yulia Angga Dewi (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This development research aims to describe the design, analyze the validity, and practicality of interactive digital comic learning media oriented towards local wisdom.Tri Hita Karana the material our earth is threatened with danger in chapter 7 of the subject of science for grade VI students. This research was conducted at Elementary School in the Gugus III area of ​​Buleleng District. This research is a type of development research (Research and Development) which uses the ADDIE model with 5 stages, namely analysis, design, development, implementation, and evaluation. However, in this study the ADDIE stages were carried out only up to the implementation stage. This interactive digital comic was created with the help of the application Canva, Pinterest, Quizizz and Heyzine Flipbook. The material is presented in a structured and interactive manner in the form of illustrated stories with human cartoon characters that are suitable for children. The media validity test obtained a result of 0.93, and the material validity obtained a result of 0.92, while the language validity obtained a result of 0.94. These results indicate that digital comics have a